(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
Solar photo-voltaic system, with a reputation being inexhaustible and environmentally benign, has been widely used for power generation. The cost competitiveness of solar PV is likely to get even more obvious, particularly when compared with the continuous rising of conventional fuel prices and the rapid decline of PV module prices. Furthermore, the policies of India are conducive to the development of solar projects. But solar PV suffers from its intermittent characteristics. Windmill produces power when the speed of wind blows beyond the cut-in speed. The kinetic energy of the wind is captured and by the application of the turbine and generator set, it converts into useful electrical energy. The energy output from this kind of power plants is dependent upon the wind speed. The proposed scheme integrates Solar PV and Windmills to increase the reliability of the power supply. As both solar PV and wind energy are intermittent, battery banks are placed to realize the reliability of the supply. The system operates on standalone mode. It is evident from various studies that, in the Leh, Ladakh region wind and Solar power production complement each other. During the summer season or sunny days, the Solar PV share a larger portion of generated power whereas in the winter season or cloudy day the large portion of power will be delivered by the Wind mill. The excess power after meeting the load demand will be stored in the battery bank and that stored energy will be utilized when the combined operation of Solar PV And Windmill are not able to meet the load demand. The proposed scheme evaluates the performance of such a scheme and aims to optimize the system.